The Role of Macrophages in the Pathogenesis of SARS-CoV-2-Associated Acute Respiratory Distress Syndrome - Kosyreva, Anna; Dzhalilova, Dzhuliia; Lokhonina, Anastasia; Vishnyakova, Polina; Fatkhudinov, Timur (Frontiers in Immunology, 2021)
Macrophages are cells that mediate both innate and adaptive immunity reactions, playing a major role in both physiological and pathological processes. Systemic SARS-CoV-2-associated complications include acute respiratory distress syndrome (ARDS), disseminated intravascular coagulation syndrome, edema, and pneumonia. These are predominantly effects of massive macrophage activation that collectively can be defined as macrophage activation syndrome. In this review we focus on the role of macrophages in COVID-19, as pathogenesis of the new coronavirus infection, especially in cases complicated by ARDS, largely depends on macrophage phenotypes and functionalities. We describe participation of monocytes, monocyte-derived and resident lung macrophages in SARS-CoV-2-associated ARDS and discuss possible utility of cell therapies for its treatment, notably the use of reprogrammed macrophages with stable pro- or anti-inflammatory phenotypes.